Meningkatkan Aktivitas dan Hasil Belajar IPAS Melalui Model Problem Based Learning (PBL) Pada Siswa Kelas IV SD Inpres 1 Tanamodindi - Rosa Rosa; Arif Firmansyah; Herlina Herlina; Muslim A.R (JURNAL DIKDAS, 2025)
This study aims to improve students’ learning activities and learning outcomes through the implementation of the Problem Based Learning (PBL) model in IPAS learning. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were fourth-grade students of SD Inpres 1 Tanamodindi. Data were collected through observation sheets to measure students’ learning activities and learning outcome tests to assess students’ achievement. Data analysis was conducted using descriptive quantitative techniques by comparing the results of each cycle. The results showed that the implementation of the Problem Based Learning model improved students’ learning activities and learning outcomes in IPAS learning. These findings indicate that the PBL model is effective in enhancing the quality of learning in elementary school.